The Evolution of Digital Accounting and Accounting Information Systems in the Modern Business Landscape - Prasetianingrum, Septyana; Sonjaya, Yaya (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: The study aims to investigate the evolution of digital accounting and accounting information systems (AIS) in the Modern Business Landscape through a qualitative examination of the existing literature. Research Design and Methodology: Employing a systematic review approach, the research examines academic journals, books, and conference proceedings relevant to digital accounting and AIS. The selection criteria focus on publication credibility, relevance, and recency, as well as the contributions to theoretical and empirical knowledge. Data collection encompasses searching, screening, and supplementary techniques, including content analysis, citation analysis, and bibliometric analysis. Qualitative methods, such as coding, categorization, and thematic analysis, are employed to dissect and identify prevalent themes and theoretical frameworks within the literature. Findings and Discussion: The findings reveal a rich tapestry of historical progression, technological advancements, and organizational implications of digital accounting and AIS. From the automation of routine tasks to the integration of advanced analytics, digital accounting emerges as a transformative force that shapes organizational practices and informs strategic decision-making. Implications: The study underscores the foundational role of technology in shaping the trajectory of digital accounting, with consequences for efficiency, accuracy, transparency, and strategic planning within organizations.